2007
DOI: 10.1037/0096-1523.33.6.1431
|View full text |Cite
|
Sign up to set email alerts
|

The importance of information localization in scene gist recognition.

Abstract: People can recognize the meaning or gist of a scene from a single glance, and a few recent studies have begun to examine the sorts of information that contribute to scene gist recognition. The authors of the present study used visual masking coupled with image manipulations (randomizing phase while maintaining the Fourier amplitude spectrum; random image structure evolution [RISE]; J. Sadr & P. Sinha, 2004) to explore whether and when unlocalized Fourier amplitude information contributes to gist perception. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
84
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 78 publications
6
84
1
Order By: Relevance
“…Fully phase-randomized scenes lack higher order scene statistics (Thomson, 1999(Thomson, , 2001a and are unrecognizable (Joubert et al, 2009;Loschky & Larson, 2008;Loschky et al, 2007). Thus, testing our hypothesis required comparison stimuli that, in contrast with phaserandomized images, did contain higher order statistical relationships such as those in natural scenes (Thomson, 2001a(Thomson, , 2001b, but, similar to phase-randomized images, were not recognizable.…”
Section: The Present Studymentioning
confidence: 95%
See 4 more Smart Citations
“…Fully phase-randomized scenes lack higher order scene statistics (Thomson, 1999(Thomson, , 2001a and are unrecognizable (Joubert et al, 2009;Loschky & Larson, 2008;Loschky et al, 2007). Thus, testing our hypothesis required comparison stimuli that, in contrast with phaserandomized images, did contain higher order statistical relationships such as those in natural scenes (Thomson, 2001a(Thomson, , 2001b, but, similar to phase-randomized images, were not recognizable.…”
Section: The Present Studymentioning
confidence: 95%
“…Several studies have shown that incrementally destroying the higher order image statistics of scenes by incrementally randomizing their phase spectra, while preserving as masks, as compared with normal scenes, is that phaserandomized scenes are less recognizable; that is, more recognizable masks produce more masking-a phenomenon known as conceptual masking (Bachmann, Luiga, & Põder, 2005;Intraub, 1984;Loftus & Ginn, 1984;Loftus, Hanna, & Lester, 1988;Loschky et al, 2007;Potter, 1976). However, masking produced by unrecognizable texture masks could not be explained that way.…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations